Production and Screening of Streptomyces-Extracellular Chitinase - Ibrahim Sani; Aminu Argungu Umar; Evelyn Uzoamaka Udeze (Journal La Lifesci, 2021)
The aim of this research was to produce Streptomyces-extracellular chitinase and screen its antifungal activity on a clinically isolated Candida albicans. The Streptomyces were isolated from an agricultural farmland; they were identified and screened for the chitinase production. Effects of time, temperature, pH and nitrogen sources on the chitinase production were determined using standard methods. Ammonium sulphate precipitation was used to partially purify the chitinase. Protein concentrations were determined spectrophotometrically using bovine serum albumin as standard. Agar-well diffusion method was used to evaluate the antifungal activity of the chitinase on C. albicans. The isolated Streptomyces were of three (3) strains, and all the strains are Gram positive, catalase positive, oxidase positive while, Strain A and C are indole positive and only Strain B is citrate positive. The maximum chitinase production was at 72 h, 40°C and when yeast extract was used as the nitrogen source. Ammonium sulphate (80%) precipitation yielded the highest enzyme activity of 39.0U/ml. The maximum enzyme activity was observed at temperature of 40oC, pH 5.5 and 1.0% colloidal chitin (substrate). The partially purified chitinase showed a zone of inhibition of 20.11 ± 1.26 mm against the Candida albicans. This result has no significant difference (P>0.05) when compared with that of the standard drug (Fluconazole) with 21.42 ± 0.08 mm zone of inhibition. These findings suggest that Streptomyces at favourable conditions produce chitinase, and this enzyme can be used as an antifungal agent on Candida albicans and other chitin containing fungi.